Effects of noise exposure on occupational stress among palm oil mill workers in Malaysia - Roya, Latifi Naeini (2015)
Introduction: Although the foremost concern of chronic excessive noise exposure has been the potential of auditory effects, but noise as an ambient stressor cause a series of non-auditory effects which cannot be overlooked. The environmental noise resulted from operating machineries usually exceeded the NIOSH (1999) recommended exposure limit of 85 dB (A) and as one of the major environmental stressors in palm oil mills is always considered as a key factor in creation of a series of complaints and develop occupational stress as a chronic disorder among palm oil mill workers. The present study will promote a better understanding of the non-auditory effects of noise experienced by palm oil mill workers and, identify the workplace and personal factors contributing to the occupational stress. Objective: The general objective of this study was to determine the association between personal noise exposure and occupational stress among palm oil mill workers in Malaysia. The study had 9 specific objectives. Objectives 1, 2 and 3 were to determine the environmental sound levels at each section and to determine the average of personal noise exposure of the respondents at each mill and in each section and compare the personal noise exposure levels between the workers of noisy and normal working area. Objectives 4, 5 and 6 were to determine the prevalence of stress (PSI), average of personal stress levels and compare the mean of personal stress level between high exposed and low exposed groups. 7th specific objective of the study was to determine the salivary α-amylase concentration level (U/ml) among highexposed and low-exposed groups and compare the α-amylase concentrations (U/ml) between the two groups in resting and stimulated condition. Finally last two specific objectives of the study were to determine the relationship between stress indicators (PSI (O’Donnell) and salivary α-amylase activity) with PNE and to determine the relationship between selected risk factors with stress levels. Methodology: This experimental research was implemented through a cross sectional study started since 2012 and took for two years. The study was conducted at seven sections of five selected palm oil mills and 173 participants were invited through purposive sampling based on inclusive criteria. Different materials and techniques were used in order to determine the occupational stress level among the workers, including salivary alpha amylase (sAA) assay kit as the physiological (bio marker) indicator and personal stress inventory (PSI) as the psychological indicator. Validation and reliability of the translated version of PSI (O’Donnell) shows that the questionnaire was capable in assessing psychological symptoms of occupational stress (Cronbach’s alpha= 0.96). Moreover, environmental sound level (ESL) meter (Model: Lutron SL-4112) and dosimeter (Model: wireless110A) were used to evaluate ambient noise level and personal noise exposure (PNE) level respectively. Results: The results indicated that, even though the environmental sound level in most of the sections exceeded the action level (85dB (A)), but the average of PNE level in all of the sections is below the action level (85 dB (A)). Meanwhile, there is no significant different in PNE mean between workers from noisy and normal working area (t=- 1.742, p=0.083). Finding shows that the mean of PSI among high-exposed group (33.96 (19.10)) is higher than low- exposed group (14.48 (11.61)) and there is a significant different in PSI score level between two groups (t=-5.125, p<0.001). Moreover the outcome shows that there was a significant association between PSI score and PNE level (χ2=36.185, p<0.001). Salivary α-amylase (sAA) concentration was compared individually among two groups. The results indicated that only in working condition, there is a significant different in sAA between high-exposed and low exposed groups (t=-3.983, p<0.001). Also findings shows that there is a significant association between PNE level with sAA concentration variation (r=0.770**, p<0.001). Similarly, the results of the PSI score support the finding about sAA and shows that, there is a significant association between PNE and PSI score among palm oil mill workers (rs=579**,p<0.001). Personal factors have no significant relationship with stress level in this study but among work related stressors, only work shift (χ2 =13.497,p<0.005), PPE usage (χ2=14.353, p<0.005) and PNE level (χ2= 36.185, p<0.005) are the three occupational risk factors significantly associated with occupational stress. Conclusion: The significant association between PSI and PNE,identified PNE as a significant predictor for occupational stress. The increment of sAA concentration in working situation among both groups shows that generally the workers were experiencing stress condition after 8 working hours but the difference is only significant among exposed group. Meanwhile the significant association between sAA concentration and PNE shows that, sAA could be a potential indicator of physiological symptoms of occupational stress. None of the personal stressors has significant association with occupational stress and only noise exposure, PPE using and work-shift, are identified as the significant predictors of occupational stress among palm oil mill workers.